Ethical considerations in quality improvement: key questions and a practical guide - Michael Dunn; Jill Bailey; David Francis Hunt; Guy Harrison (BMJ Open Quality)
Quality improvement (QI) provides a rigorous and innovative approach to improving patients lives in the healthcare system. Still, it can pose challenges in understanding what ethical considerations apply to some projects to minimise the possibility of patient harm or prevent other ethical wrongs and potential staff burden. While many commentaries discuss the extent to which QI ethics should match research ethics, there is minimal literature regarding what QI project teams should do when considering ethics at the planning stage. This paper provides a practical walkthrough of some of the ethical considerations across the breadth of QI projects, starting from some of the key questions when planning a QI project and a guide for the different ethical considerations that may apply.